2021
DOI: 10.6023/cjoc202106021
|View full text |Cite
|
Sign up to set email alerts
|

Development of Nickel-Catalyzed Cross-Coupling of Alcohol Derivatives to Construct Carbon-Carbon Bonds

Abstract: Transition metal-catalyzed cross-coupling reactions for building carbon-carbon bonds have received extensive attention due to their high efficiency and selectivity. In recent years, electrophiles which containing C(sp 3 )-O bonds have been used to replace organic halides in cross-coupling reactions for the construction of C(sp 3 )-C bonds, due to their advantages of commercial availability or facile synthesis, high reaction selectivity, and environmental friendliness. Among those reported highly efficient cata… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 196 publications
0
3
0
Order By: Relevance
“…In 2017, it was reported that the nickel complex could be used to catalyze the azide−alkyne cycloaddition (NiAAC) to generate 1,5-disubstitued 1,2,3-triazoles at room temperature. 60 Attracted by this new effective reaction and robust Ni catalyst, 61 we, as a group focusing on the development of new efficiently alkyne-based click polymerization, anticipated that it could be developed into a new click polymerization. Indeed, through systematic investigation, a highly efficient nickel-catalyzed azide−alkyne click polymerization (NiAACP) was successfully established.…”
Section: ■ Introductionmentioning
confidence: 99%
“…In 2017, it was reported that the nickel complex could be used to catalyze the azide−alkyne cycloaddition (NiAAC) to generate 1,5-disubstitued 1,2,3-triazoles at room temperature. 60 Attracted by this new effective reaction and robust Ni catalyst, 61 we, as a group focusing on the development of new efficiently alkyne-based click polymerization, anticipated that it could be developed into a new click polymerization. Indeed, through systematic investigation, a highly efficient nickel-catalyzed azide−alkyne click polymerization (NiAACP) was successfully established.…”
Section: ■ Introductionmentioning
confidence: 99%
“…However, because of the poor leaving ability of the hydroxyl group, direct displacement of the hydroxyl group is laborious, and only π-activated allylic and benzylic alcohols are effective for transition-metal-catalyzed arylation reactions. Therefore, alternatively, activated derivatives of simple aliphatic alcohols are applied in several transition-metal-catalyzed deoxygenative C­(sp 3 )–C­(sp 2 ) couplings with aryl halides. Apparently, these protocols require preanchored activating groups, and their synthesis and purification sequences increase the operational complexity and cost.…”
mentioning
confidence: 99%
“…17 A nickel-catalyzed cross-coupling reaction was proposed via a one-step alcohol deoxygenation pathway, whereas the method did not tolerate ketone derivatives (Scheme 1B). 18 In our own studies, we reasoned that transition metal catalysts could lower the activation energy of ketones as well as hydrazone, and therefore can achieve direct deoxygenation under mild conditions.…”
mentioning
confidence: 99%